Linking Human Resource Practices to Employee Resiliency: The Moderating Role of Transformational Leadership - Michael F. Gibaga; Reynaldo J. Villegas; Emmanuel P. Paulino; Sharon-Jully P. Untalan (APPS Publications, 2025)
The study aims to explore the intricate relationship between Human Resource Practices (HRP) and Employee Resilience (ER) within the high-pressure environment of the Philippine Business Process Outsourcing (BPO) industry. Beyond just establishing a direct link, the research specifically seeks to examine the moderating role of Transformational Leadership (TL). The goal is to determine if the presence of inspiring and supportive leadership behaviors significantly amplifies the positive impact that standard HR initiatives have on an employee’s ability to bounce back from workplace stressors. The researchers employed a quantitative research design, gathering data from a substantial sample of 523 BPO employees in the Philippines. To analyze the complex interactions between these organizational variables, the study utilized Structural Equation Modeling (SEM). This statistical technique allowed the researchers to test the structural relationships within a moderated framework, ensuring a robust validation of how HR systems and leadership styles collectively influence the latent construct of resilience. The results demonstrate that HR Practices significantly enhance Employee Resilience, confirming that structured organizational support is a foundation for workforce stability. However, the findings also reveal a critical nuance: HR initiatives alone are insufficient in high-stress service environments. The relationship is considerably strengthened when Transformational Leadership is present. This suggests that while HR provides the tools for resilience, it is the leaders who unlock the full potential of those strategies, ultimately reducing burnout and sustaining performance in dynamic settings. The novelty of this research lies in its integration of HRP, leadership behavior, and resilience into a single, cohesive moderated framework. By moving beyond isolated variables, the study advances Human Resource Management literature by demonstrating how organizational systems and relational mechanisms (leadership) must work in tandem. Furthermore, it provides specific, actionable guidance for the BPO sector, highlighting that the alignment of HR strategy with leadership development is the key to cultivating a workforce capable of withstanding the unique challenges of the industry.